Pre-treatment of sugarcane bagasse for conversion to single cell protein through one-step enzymatic hydrolysis and bioconversion - Lourens, Veronica (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.